Talent selection: Making decisions and prognoses about athletes - Lath, F.; den Hartigh, R.; Wattie, N.; Schorer, J. (Talent identification and development in sport. International perspectives, 2021)
In this chapter, we focus o n an almost forgotten actor in talent research - the coach w ho has to m ake decisions on the future potential of children at different developmental stages. Coaches must make prognoses, often on the bases of little Information, about how these young athletes will perform when they are at their prime. To guide you through this chapter, Figure 4.1 shows a summary of the process we will discuss. As we will argue in the first part of this chapter, making prognoses on athletes is not an easy task. In the second part, we provide the reader with an overview of current know ledge on the 'coaches' eye' for identifying talent. We then place the coaches' eye within a broader psychological framework of decision making. Finally, we consider how knowledge from decision making research might improve our understanding of talent selection processes in the future.